E-MAS BSI MOBILE: KAJIAN LITERATUR SISTEMATIS - Syarif Nasution, Ahmad; Siddik, Ega; Hermawan, Indra (JURNAL ILMU MANAJEMEN DAN KEWIRAUSAHAAN (JIMK), 2023)
With the E-Mas feature, customers can easily perform transactions such as gold savings, gold pawning, and gold installments online. This research is a type of library research using a systematic literature review methodology, which involves collecting, evaluating, integrating, and presenting findings from various studies related to a specific topic. Therefore, this research consists of three stages: collection, evaluation, and presentation. The collection stage is conducted using the Publish or Perish search engine with the Google Scholar database. The keywords used are “E-Mas BSI Mobile,” with a time range from 2021-2023. The research results reveal that the practice of digital gold investment in the E-Mas BSI Mobile product at Bank Syariah Indonesia does not contradict Sharia economic principles and identify the factors influencing consumers to transact E-Mas, along with some shortcomings in its marketing.